Pengaruh Kecerdasan Emosional Dan Budaya Organisasi Terhadap Kinerja Perawat : Studi Pada Perawat IGD dan ICU RSB Guluh / BLUD Kolaka SMS Berjaya - Monika Rannu; Ismanto Ismanto; Hanif Kurniadi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out: (1)Effect Of Emotional Intelligence on Organisational Culture On The Nurse Nurse Performance(Study on Emergency on nurse performance (Study on emergency room and Intensive Care nurse of Benyamin Guluh hospital/kolaka SMS Berjaya BLUD). (2) Effect of Organizational Culture on Nurse Performance (Study on Emergency room and Intensive Care Unit nurses of Benyamin Guluh Hospital/Kolaka SMS Berjaya BLUD). This study uses an approach with quantitative methods.Data collection in this study through observation, literature study and questionnaires. The population of this study ware all emergency room and intensive care unit nurses at Benyamin Guluh Hospital/Kolaka SMS Berjaya BLUD. While the sampel of this study amounted to 30 nurses with the determination of the sample using purpositive sampling with hair formula. Testing of research instruments using validity tests and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model test (outer model) and structural model testing (inner model) with Smart PLS 3.0.Based on the results of the study, it is known that the Emotional Intelligence variable has a positive and significant effect on Nurse Performance as indicated by the P-Values value of 0.005.And the Organizational Culture variable also has a positive and significant effect on Nurse Performance, this is indicated by the P-Values value of 0.037.